Realisasi model pembelajaran quantum teaching dalam meningkatkan pemahaman materi pai di SD Negeri 04 Biaro, Kecamatan Ampek Angkek, Kabupaten Agama, Provinsi Sumatera Barat - Selvia, Gita (Maliki Interdisciplinary Journal, 2024)
Islamic Education (PAI) at the Elementary School (SD) level plays a crucial role in shaping the character and spiritual values of students. Effective learning models are key to strengthening understanding of religious concepts at an early age. This article investigates the application of the Quantum Teaching learning model in the context of PAI education at SD Negeri 04 Biaro. The Quantum Teaching method offers an innovative approach that integrates aspects such as active interaction, encouragement of reflective thinking, and the use of cognitive techniques to stimulate deeper learning processes among students. This study employs a qualitative descriptive approach with interviews and library research as data collection techniques. The research findings indicate that, while the Quantum Teaching model can enhance students’ understanding of PAI subjects, there are challenges such as inadequate facilities and resources, as well as complexities in preparation that require considerable time. The study suggests the need for better strategies and adequate support in terms of facilities, resources, and sufficient expertise to optimize the implementation of the Quantum Teaching model in PAI education at SD Negeri 04 Biaro.